Comparison of trend analysis of varicella zoster disease burden between China and the world 1990–2021 and disease burden forecast 2030 - Chang, Zhichun; Li, Huale; Li, Yanfang; Qin, Ting; Hu, Mingren; Yang, Xinjing; Li, Jun; Xie, Yufeng (Frontiers in Public Health, 2025)
ObjectivesThis study aims to analyze temporal trends in the age- and sex-specific burdens of varicella zoster virus (VZV), including incidence, prevalence, mortality, and disability-adjusted life years (DALYs) in China from 1990 to 2021, and to predict the burden of varicella zoster in China for 2030 by comparing the trends with the global burden of the disease.MethodsData from the Global Burden of Disease database (1990–2021) were used to analyze the characteristics of varicella zoster virus (VZV) burden in China and globally, including trends in incidence, prevalence, mortality, and disability-adjusted life years (DALYs). The average annual percentage change (AAPC) and its corresponding 95% confidence interval (95% CI) were calculated using Joinpoint to assess the VZV burden trends. A comprehensive comparative analysis of the differences in VZV burden between China and the global population was conducted across multiple dimensions, including age, gender, and time period. Additionally, an autoregressive integrated moving average (ARIMA) model was used to predict the VZV trend from 2021 to 2030.ResultsBetween 1990 and 2021, the age-standardized incidence rate (ASIR) of varicella zoster in China decreased from 1,274.93/100,000 to 1,270.58/100,000, while the global ASIR increased from 1,244.05/100,000 to 1,248.59/100,000. In China, the age-standardized prevalence rate (ASPR) decreased slightly from 72.27/100,000 to 72.03/100,000, whereas the global ASPR rose from 66.67/100,000 to 67.16/100,000. The age-standardized disability-adjusted life year rate (ASDR) in China decreased significantly, from 17.68/100,000 to 4.66/100,000, while the global ASDR decreased from 19.28/100,000 to 12.31/100,000. Similarly, China’s age-standardized mortality rate (ASMR) declined significantly, from 0.40/100,000 to 0.05/100,000, while the global ASMR decreased from 0.35/100,000 to 0.19/100,000. Over the same period, the average annual percentage change (AAPC) of ASIR, ASPR, ASMR, and ASDR in China was −0.0056, −0.0131%, −6.84%, and −4.24%, respectively, while the global AAPC for these metrics was 0.0119, 0.0183, −1.97%, and −1.42%, respectively. Additionally, age and gender had a significant impact on the burden of varicella zoster. The trends in ASIR and ASPR were notably influenced by age, while ASMR and ASDR exhibited a significant increasing trend with age. Projections indicate that the ASDR of varicella zoster in China will continue to decrease by 2030, while the ASIR, ASPR, and ASMR are expected to remain stable.ConclusionBetween 1990 and 2021, the incidence, prevalence, mortality, and DALYs of VZV in China demonstrated a declining trend, reflecting a relative reduction in the VZV burden. Women are more susceptible to VZV infection and face a higher risk of mortality than men. In contrast, the global disease burden remains higher than that in China. Projections suggest a slight decrease in the VZV burden in China by 2030. However, due to the country’s large and aging population, VZV will continue to pose a significant public health challenge.